2022
DOI: 10.3390/metabo12020158
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Changes in Larvae of Predator Chrysopa sinica Fed on Azadirachtin-Treated Plutella xylostella Larvae

Abstract: Biological control is a key component of integrated pest management (IPM). To suppress pests in a certain threshold, chemical control is used in combination with biological and other control methods. An essential premise for using pesticides in IPM is to ascertain their compatibility with beneficial insects. Chrysopa sinica (Neuroptera: Chrysopidae) is an important predator of various pests and used for pest management. This study was intended to analyze metabolic changes in C. sinica larvae after feeding on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…The high efficiency and relative safety have made azadirachtin a botanical pesticide for pest control in the past decades. Azadirachtin has a high efficiency in a lot of pests and has biological activity against Plutella xylostella, Ostrinia furnacalis, brown rice planthopper, Bemisia argentifolii, Agrilus planipennis, and other pests. Azadirachtin can significantly inhibit the growth and development of insects, including reduced diet intake, delays in development of larvae and nymphs, permanent larvae, incomplete ecdysis, malformed pupae and adults, sterile eggs, and reduced fecundity. , The study found that azadirachtin did not compete with ecdysone or bind to the ecdysone receptor.…”
Section: Discussionmentioning
confidence: 99%
“…The high efficiency and relative safety have made azadirachtin a botanical pesticide for pest control in the past decades. Azadirachtin has a high efficiency in a lot of pests and has biological activity against Plutella xylostella, Ostrinia furnacalis, brown rice planthopper, Bemisia argentifolii, Agrilus planipennis, and other pests. Azadirachtin can significantly inhibit the growth and development of insects, including reduced diet intake, delays in development of larvae and nymphs, permanent larvae, incomplete ecdysis, malformed pupae and adults, sterile eggs, and reduced fecundity. , The study found that azadirachtin did not compete with ecdysone or bind to the ecdysone receptor.…”
Section: Discussionmentioning
confidence: 99%
“…During pathway enrichment analysis, the following parameters were applied: the model organism library selected was Drosophila melanogaster , and statistical comparisons were performed using the hypergeometric test . The pathways that exhibited significant effects were determined based on their respective P -values, following the approach described by Zhang et al (2022) . Some of the metabolites (pyridoxal, valine, quinolinic acid, arginine, hypoxanthine, and citric acid) belonging to different pathways were not enriched during pathway analysis.…”
Section: Methodsmentioning
confidence: 99%
“…FC was calculated as the ratio of the peak area of parasitized and non-parasitized groups. Additionally, the screening criteria for differential metabolites was the VIP values from the OPLS-DA model > 1 and the p -value from the Student’s t -test < 0.05, based on the previous reports [ 36 , 37 , 38 ]. Here, the default 7-fold cross-validation was applied with 1/7 of the samples being excluded from the mathematical model in each round, to guard against overfitting.…”
Section: Methodsmentioning
confidence: 99%